EDUKASI LITERASI KEUANGAN DIGITAL BAGI GENERASI Z DI SMK DDI PAREPARE - Husain, Hartina; Zaitun, Zaitun; Nisardi, Muhammad Rifki; Resky, Aprizal; Kusnaeni, Kusnaeni; M.R, Andi Oxy Rayhan; Herlambang, Dwicki; Nurlia, Nurlia (Jurnal Abdi Insani, 2024)
Generation Z who are used to technology have digital financial literacy problems. They lack basic financial understanding, are prone to deceptive online offers, and are vulnerable to cyber fraud. This can result in difficulty achieving financial goals and being in debt. It is important to increase Gen Z's digital financial literacy through education, campaigns and developing educational applications so that they become a financially independent generation. This is the background for implementing this service, where the aim of this service activity is to introduce and integrate digital financial literacy education from an early age, we can help the younger generation to become more financially independent and skilled in managing their money in this digital era. It is hoped that this digital financial literacy education will be able to increase the understanding of generation Z, or in this case, students at SMK DDI Parepare, in increasing awareness about the importance of managing finances. The methods that will be used include webinars, discussions, questions and answers to student participants (i) at SMK DDI Parepare. This training was proven to be effective in increasing the knowledge of generation Z at DDI Parepare Vocational School regarding digital financial literacy, this was shown by the results of the pretest posttest difference test).